The organization of Philippine vocal and instrumental scores in selected academic music libraries in Metro Manila a survey - Baradas, Josephine Cecilia Lontoc 1963-
Majority of the librarians/catalogers have come up with thier own improvised subject headings for Philippine music scores. The subject authority lists, i.e., Sears List and LCSH seem to be insufficient in that the music libraries needed to improvise the subject headings assigned to Philippine music scores and music books. Majority of the libraries have classified their Philippine music collection of scores as Filipiniana mateials. Two (33 percent) libraries used the DDC system while three (50 percent) libraries make use of the LCC scheme. One (17 percent) library make use of an improvised classification scheme.